In Your Face(t)—Personality Traits Interact With Prototypical Personality Faces in Economic Decision Making - Weiß, Martin; Paelecke, Marko; Hewig, Johannes (Frontiers in Psychology, 2021)
In everyday life, assumptions about our peers’ as well as our own personality shape social interactions. We investigated whether self-rated personality and inferences drawn from partners’ faces influence economic decisions. Participants (N = 285) played the trust game in the role of the trustor as well as the ultimatum game in the role of the proposer and interacted with trustees and receivers represented by prototypical personality faces. Participants also evaluated both their own traits and the personality of the faces. In the trust game, trustees represented by faces rated higher on agreeableness yielded higher transferred amounts. This effect was more pronounced for trustors low on dispositional trust, whereas trustors high on dispositional trust did not relate their decisions to the faces. Trustees represented by faces rated higher on conscientiousness yielded higher transferred amounts only for trustors high on dispositional anxiety. In the ultimatum game, receivers represented by faces rated higher on conscientiousness yielded lower offers only for proposers high on dispositional assertiveness. These results extend previous findings on the inferences drawn from facial features and the influence of personality on decision-making. They highlight the importance of considering the personality of both interaction partner, as well as potential interactions of players traits.